Why Young Women Who Use Opioids Are at Risk for Rape: The Impact of Social Vulnerabilities and Sexually Coercive Drug Using Contexts - Jessell, Lauren (Violence against women, 2024)
This study tests a theoretically informed model to understand why women who use opioids (WWUO) are at risk of rape while using drugs. Structured interviews were conducted with 168 WWUO. Three domains were hypothesized to increase risk: the sexually coercive context of drug use, women's social vulnerability, and drug use severity. Logistic regression examined the odds of being raped by domain. One-third of WWUO had been raped while using drugs. The sexually coercive context and social vulnerability domains significantly increased women's odds of being raped. Prevention efforts should target social and contextual factors.